The Antioxidant Capacities and Antimicrobial Activities of Some Salvia L. Seeds - Kurşat, Murat; Kırbag, Sevda; Emre, Irfan; Sönmez, Pınar Erecevıt; Emre, Mustafa Yunus; Ökkeş; Civelek, Şemsettin (My University, 2023)
The goal of present study is to find the penolic contents, antioxidant activities and antimicrobial capacities in the seeds of five Salvia L. taxa two of which are endemics (Salvia euphratica var. leiocalycina and Salvia euphratica var. euphratica). The flavonoid and phenolic acid are determined by using HPLC while the antioxidant activities are determined based on different methods. Also, the antimicrobial activities of some Salvia species are determined by using the well agar method. The current study found that the studied Salvia species have low flavonoid. It has been found that Salvia euphratica var. euphratica has high vanillic acid, ferulic acid and rosmarinic acid among the studied taxa. Similarly, it has been found that Salvia euphratica var. euphratica has high DPPH and ABTS radical scavening capacity in all concentrations. It has been also found that Salvia euphratica var. euphratica has highest total phenolic content (372,63±0,87 µgGAE/mg) whilst Salvia tricholoda has low total phenolic content (46,41±1,71 µgGAE/mg). In addition, this study demonstrated that Salvia tricholoda has lowest metal chelating activity (37,35±0,51%). Furthermore, present study found that the lipid peroxidation levels of the studied Salvia taxa are between 18,21±0,37 mg/kg and 21,03±0,22 mg/kg while it has been found that the antibacterial properties of the Salvia taxa under study are altering.
Keywords: Antimicrobial Activity; Phenolics; Antioxidant Capacity; Salvia L